Association between maternal hemoglobin concentration levels and preterm birth clinical subtypes: A retrospective, observational, multicenter study - Peiran Chen; Yi Mu; Yanxia Xie; Yanping Wang; Zheng Liu; Mingrong Li; Juan Liang; Jun Zhu (PLoS ONE, 2026)
Background As a routine component of antenatal care, hemoglobin (Hb) testing can detect underlying abnormalities in pregnant women, thereby guiding clinical interventions. However, Hb concentration levels and trajectories during pregnancy and the association with preterm birth remain contentious owing to the unclear mechanisms involved. We aimed to evaluate the association between Hb concentration levels and preterm birth clinical subtypes in each trimester, and to assess the association between Hb trajectories and preterm birth clinical subtypes in pregnancy. Methods This is a secondary analysis of a previously conducted cohort which is a retrospective, observational, multicenter study. The study included women with singleton live births between 28 and 45 gestational weeks from 2012 to 2021 who had undergone at least one Hb test before 37 weeks. Poisson regression with a robust variance estimator was used to estimate the association between preterm birth and Hb concentration levels measured at a given time. We included women from the overall sample who initiated antenatal care before 14 weeks and who had at least one Hb test in each trimester for analysis of their Hb trajectory. Multivariable logistic regression was used to estimate the association between preterm birth and Hb trajectories. Outcome measurements included preterm birth and clinical subtypes. Results We included 72,139 women in this analysis, the preterm rate, spontaneous preterm rate and iatrogenic preterm rate were 6.73%, 4.12% and 2.50% respectively. In relation to an Hb cutoff value of 110 g/L in the third trimester, a “L” shape of curve was observed in the association between spontaneous preterm and Hb concentration, and a “U” shape of curve was observed in the association between preterm, iatrogenic preterm and Hb concentration. 17,101 women were enrolled in the trajectory analysis. A constant high Hb concentration trajectory was associated with an increased risk of preterm and iatrogenic preterm (odds ratio with its 95% Confidence Interval, OR[95%CI] were 1.22[1.05,1.42] and 1.35[1.03,1.78] respectively), and a constant low Hb concentration trajectory was associated with an increased risk of spontaneous preterm (OR[95%CI], 1.30[1.03,1.64]). Conclusion The association between preterm birth and both low and high Hb levels should not be ignored. Women with anemia in late pregnancy should be aware of iatrogenic and spontaneous preterm birth, and women with high Hb concentrations should be aware of iatrogenic preterm birth. Constantly high Hb level may warrant an alert for iatrogenic preterm birth, and constantly low Hb level may warrant an alert for spontaneous preterm birth.